Analysis of Possibilities of Increasing the Spanned Distance Using EDFA and DRA in DWDM System - Tomas Ivaniga; Petr Ivaniga; Jan Turan; Lubos Ovsenik (Communications - Scientific letters of the University of Zilina, 2017)
The aim of this article is a comparison of the EDFA (Erbium Doped Fibre Amplifier) and the DRA (Distributed Raman Amplifier) in a fully optical communication system, working on a specific wavelength. The amplifiers are compared based on their position in the optical loop and are evaluated according to the Q-factor and bit error rate (BER). In the case of the DRA, the accomplished distance was smaller, while changing the optical power in CW (Continuous Wave) to attain better BER. In the application of the EDFA a similar optical loop was created, as well, while the basic parameter for comparison was a bit speed. For the EDFA the bit speed was changed from 10 to 15 Gbps. For the DRA the change was in the power from 1 to 3 mW with the bit speed kept at 10 Gbps. This publication also focuses on the need for such application of a transfer system in a software environment. It would enable examination and research and consequently a minimising of the influence of non-linear effects impacting the particular WDM (Wavelength Division Multiplex) system.